Vacuum measurement of He based on Fabry-Perot cavity and constant pressure reference. (December 2021) - Jia, Wenjie; Xi, Zhenhua; Guo, Meiru; Fan, Dong; Ren, Zhengyi; Cheng, Yongjun
Abstract: In order to reduce the uncertainty of the gas refractive index measurement device based on laser interferometry. A measuring method based on constant pressure reference point was proposed. Combined refractive index of reference point and variation of laser frequency measured by beat frequency, the ratio of refractive index of two cavities can be obtained by inversion. In this paper, the refractive index of He was measured when the pressure is 10 4 –10 5 pa. The relative deviation of result between theory and test is less than 1.7 × 10 −6 and the measurement uncertainty is 1.48 × 10 −9 . The method of refractive index measurement based on constant pressure can reduce the uncertainty effectively, which is great significance to the establishment of primary quantum vacuum metrology standard.